Does Islamic Microfinance Go beyond the Self-employability? An Appraisal from Lahore, Pakistan. (November 2016) - Mahmood, Hafiz Zahid; Abbas, Kausar; Fatima, Mehreen; Asghar, Shumaila
Abstract: Unemployment is a syndrome which is a common feature of all developing nations. Masses are either unemployed or self-employed due to lack of opportunities and distorted public policies regarding employment generation in these countries. Microenterprises financing through microfinance institutions are playing a pivotal role in creating employment opportunities for their target households. This study observes the impact of Islamic microfinance on self, family and community employment generation activities. In this regard, data were collected from 168 clients of three pioneering Islamic microfinance institutions working in Lahore, Pakistan. The study uses descriptive analysis and probability econometric modeling to achieve its objectives. The results show that the Islamic microfinance played a significant role in starting and extending existing businesses of the target households. Moreover, it also helps households and community members to get absorbed in the microenterprises apart from borrowers themselves. Therefore, it is concluded that Islamic microfinance does go beyond self-employability.